Smart Agri-Preneurship Dimensions and Food Affordability (Global Journal of Management and Business Research, 2020)
This research sought to investigate the effect of smart Agri-preneurship dimensions on food affordability in South-West, Nigeria. Diverse literature confirmed positions of scholarly discourse regarding the relationship between smart Agri-preneurship dimensions and food affordability. Cross-sectional research design was adopted while adopted questionnaire was used to source primary data. Duly registered Agri-preneurs in South-West Nigeria were selected with a population of (2,557). Cochran, Hatzes, Butler, and Marcy formula (1997) was adopted and a reliable and valid questionnaire was tested on 558Agri-preneurs. The regressed constructs revealed a positive and significant effect of smart Agri-preneurship on food affordability. The findings indicated that smart Agri-preneurship dimensions have positive and significant effect on food affordability (Adj. R2 = 0.602, F (6,551) = 141.319, p=0.000). The study concludes that farmers should embrace smart Agri-preneurial technologies as innovations that could improve their farm yields, hence reduce the cost of production and make food output more affordable. The study recommends that the government should engage Agri-preneurs and provide partnerships that would be beneficial in improving food affordability opportunities through the adoption of smart technologies.
Keywords: farm yield; food affordability; food sustainability; smart agri-preneurship